The Influence of Green Innovation and CSR on Sustainable Development Mediated by Green Performance - Fenny Marietza; Melly Nadia (Global Financial Accounting Journal, 2021)
This study examines the effect of applying green innovation and corporate social responsibility disclosure on sustainable development mediated by green performance. This study's population were all mining and manufacturing companies listed on Indonesia Stock Exchange in 2015-2019. The sample in this study is mining and manufacturing companies that have to publish the sustainability report. This study's analytical tool is SPSS version 25 and used a process program that is integrated into SPSS. The results showed that green performance could not be a mediating variable for green innovation and CSR on sustainable development. This research provides information about the positive impacts that the company will generate to achieve sustainable development goals. With the application of green innovation and green performance, the company will be able to increase sustainable development achievement.